(untitled) (Research, Society and Development, 2022)
Pregnancy, childbirth and puerperium are unique moments in women’s lives, for this reason it becomes a subject in which they share information on social networks. In this sense, the present study aimed to: Describe the influence of a Facebook group on the pregnancy-puerperal cycle of women, through network conversation. This is a qualitative study with a Netnography design and analysis based on analytical coding, both in a Facebook group. Among the topics discussed in the group, the results are: the power of choice in decision-making about the mode of delivery, pain, recovery speed to have autonomy in the care of the newborn and experiences of past pregnancies. The findings show us the possibility of understanding the dialogues within their naturalness, by the freedom of expression provided by the network conversation on the internet. Thus, this study theme is considered innovative, given its contribution to understanding the importance of the internet and social media in the context of health, contributing to a better interaction between health services and the assisted population.